Cancer risks and benefits of hormonal contraception: a literature review and practical issues - Antonina V Ledina; Liubov' I Korolenkova; Evgenii V Ledin (IP Berlin A.V., 2019)
Aim. To provide up-to-date data on cancer risks in women who use oral hormones to protect themselves from unwanted pregnancies, since high onco-alertness is one of the most common reasons for their withdrawal. Materials and methods. To write this review a search for domestic and foreign articles in Russian and international search systems (PubMed, eLibrary, etc.) which were published in the period from 2003 to 2019 was carried out. The review included articles from peer-reviewed literature and guidelines for physicians and periodicals identified by keywords: cancer, cancer risk, hormonal contraception, hormones, non-contraceptive effects of combined oral contraceptives (COCs). Results. Hormonal contraceptives have a large number of beneficial non-contraceptive effects, particularly in relation to diseases associated with a menstrual cycle (premenstrual syndrome and premenstrual dysphoric disorder, menstrual disorders), infertility and a number of other diseases. Oral contraceptive use reduces an incidence of ovarian cancer and colorectal cancer but increases risks for cervix cancer and breast cancer. Based on the analysis of literature data, it was shown that women who have ever used hormonal contraception have a lower risk of death from all causes comparing to those who have never used them. Conclusion. To make a decision on a use of COCs patients should be examined and competently informed about benefits and risks of hormonal contraception.